Kinerja Guru SD Swasta: Analisis Peran Supervisi Akademik, Motivasi Kerja, dan Lingkungan Kerja - Felicita Yosephira Dyatamara Natasyaratri; Fakhruddin (ijd-demos, 2026)
Abstract This study aims to analyze the contribution of academic supervision, work motivation, and the work environment to teacher performance at private elementary schools in the Semarang Timur subdistrict. Using a quantitative correlational approach, this study involved a population of 148 teachers with a sample of 108 respondents determined using the Slovin formula (5% margin of error). Data were collected using a Likert-scale questionnaire and analyzed non-parametrically using Spearman’s rank correlation and Kendall’s W coefficient of concordance. Descriptive analysis results indicate that teacher performance and all independent variables fall into the “Moderate” category. The research findings partially confirm the positive and significant influence of academic supervision (r = 0.758), work motivation (r = 0.645), and work environment (r = 0.769) on teacher performance (p < 0.05), with the work environment factor being the most dominant determinant. Simultaneously, a Kendall’s W coefficient of 0.468 indicates the collective contribution of these three variables to the variance in teacher performance. In conclusion, enhancing the performance of private elementary school teachers cannot be achieved through partial measures but requires a holistic managerial approach that integrates professional supervision, motivational stimulation, and systemic improvements to the work environment ecosystem. Keywords:  Teacher Performance, Academic Supervision, Work Motivation, Work Environment, Private Elementary Schools   Abstrak Penelitian ini bertujuan untuk menganalisis kontribusi supervisi akademik, motivasi kerja, dan lingkungan kerja terhadap kinerja guru pada sekolah dasar swasta di Kecamatan Semarang Timur. Menggunakan pendekatan kuantitatif korelasional, penelitian ini melibatkan populasi sebanyak 148 guru dengan sampel 108 responden yang ditentukan melalui rumus Slovin (tingkat kesalahan 5%). Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis secara non-parametrik melalui teknik korelasi Rank Spearman dan koefisien konkordansi Kendall’s W. Hasil analisis deskriptif menunjukkan bahwa kinerja guru dan seluruh variabel independen berada pada kategori "Sedang". Temuan penelitian secara parsial mengonfirmasi pengaruh positif dan signifikan dari supervisi akademik (r = 0,758), motivasi kerja (r = 0,645), dan lingkungan kerja (r = 0,769) terhadap kinerja guru (p < 0,05), di mana faktor lingkungan kerja menjadi determinan paling dominan. Secara simultan, koefisien Kendall’s W sebesar 0,468 mengindikasikan kontribusi kolektif ketiga variabel tersebut terhadap variansi kinerja guru. Kesimpulannya, penguatan kinerja guru SD swasta tidak dapat dilakukan secara parsial, melainkan menuntut pendekatan manajerial holistik yang mengintegrasikan supervisi profesional, stimulasi motivasi, dan pembenahan ekosistem lingkungan kerja secara sistemik. Kata kunci: Kinerja Guru, Supervisi Akademik, Motivasi Kerja, Lingkungan Kerja, SD Swasta